Relative age effects in ice hockey extends to coaching - Grondin, Simon; Fortin-Guichard, Daniel; Lemoyne, Jean; Trudeau, François; Baker, Joe (Frontiers in Sports and Active Living, 2025)
Date of birth influences the chances of success in sports. Compared to players born just before a cutoff date for marking the admissibility in a category (age groups), players born soon after are overrepresented. However, it is not yet known whether the effect of date of birth in sports applies beyond the players' active participation in the game. The aim of the study was to determine whether there is a date of birth effect among ice hockey's coaches. The birthdates of 3,380 coaches in minor league hockey for the 2023–2024 season were obtained from Hockey Québec. The investigation indicated that people born in the first half of the year were more likely to become minor hockey coaches than those born in the second half. This significant birthdate effect is observed with coaches born in 1980s (53.42% vs. 46.58%) and after 1989 (55.73% vs. 44.27%), but not with coaches born before 1980 where the effect tended to reverse. This finding is interpreted as a consequence of the birthdate effect during the development as a hockey player and suggests a loss of potential coaches to the ice hockey system.